Water stress, temperature regimes and light control induction, and loss of secondary dormancy in Brassica napus L. seeds. Issue 3 (6th June 2017) - Soltani, Elias; Gruber, Sabine; Oveisi, Mostafa; Salehi, Nader; Alahdadi, Iraj; Javid, Majid Ghorbani
Abstract: This study investigated the induction and loss of dormancy in oilseed rape ( Brassica napus ). Twenty genotypes were preliminary screened; from these, two genotypes, RGS003 and Hayola 308, which possess high potential for dormancy induction (HSD) and medium potential to induce secondary dormancy (MSD), were selected. The stratification of seeds at alternating temperatures of 5–30°C (in dark) significantly relieved secondary dormancy, but dormancy was not fully released. The ψb (50) values were −1.05 and −1.06 MPa for the MSD and the HSD before dormancy induction. After inducing dormancy, the ψb (50) values for the MSD and the HSD were increased to −0.59 and −0.01 on day 0 stratification at 20°C. The hydrothermal time (θHT ) value was low for one-day stratification for HSD in comparison with other stratification treatments. Water stress can induce dormancy (if the seeds have the genetic potential for secondary dormancy) and warm stratification (in dark) can only reduce the intensity of dormancy. The seeds with a high potential of dormancy induction can overcome dormancy at alternating temperatures and in the presence of light. It can, therefore, be concluded that a portion of seeds can enter the cycle of dormancy ↔ non-dormancy. The secondary dormant seeds of B. napus cannot become non-dormant in darkness, but the level of dormancy may change from maximum (after water stress) to minimum (after warm stratification). It seems that the dormancy imposed by the conditions of deep burial (darkness in combination with water stress and more constant temperatures) might be more important to seed persistence than secondary dormancy induction and release. The dormancy cycle is an important pre-requisite in order to sense the depth of burial and the best time for seed germination.